PERBANDINGAN MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN MODEL ARTIKULASI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BIOLOGI DI SMP NEGERI 3 SUNGGUMINASA KAB. GOWA - Fitri Febiyanti Mansyur; Salahuddin Salahuddin; Eka Damayanti (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
This thesis discusses the comparison of biology learning outcomes through the application of the Snowball Throwing learning model with the Articulation model to students VIIA class and VIIB SMP Negeri 3 Sungguminasa. The formulation of the problem in this research is how the students' learning outcomes by using the Snowball Throwing learning model? What is the learning outcomes of students using the Articulated learning model? Are there any differences in student learning outcomes using the Snowball Throwing model with the Articulation model? Class VII SMP Negeri 3 Sungguminasa Gowa regency in the subject of this research cell aims to obtain information about the results of biology students learning grade VII SMP Negeri 3 Sungguminasa academic year 2017/2018 learners are taught through the model of Snowball Throwing and learners are taught through the model of Articulation , and to know the difference of learning outcomes of learners who are taught through the Snowball Throwing model with the Articulation model. This research is Quasi Experimental Design research with Noquivalent Control Group Design research design. The population of this study are all students of class VII SMP Negeri 3 Sungguminasa which amounted to 353 people while the sample is VIIA class amounted to 33 people and class VIIB amounted to 33 people. The research instrument used in this study is the test of student learning outcomes. Data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, obtained the average of the two groups, the experimental class I is taught by using the learning model of Snowbal Throwing of 78.15. In the experimental class II that was taught using the Articulation learning model of 71.5. While based on result of inferential analysis using independent sample t-test obtained p value equal to 0,003 smaller than at α equal to 0,05 (p <0,05) hence can be concluded that H0 is rejected. So there is a significant difference between the Snowball Throwing model and the Articulation of the biology learning outcomes of learners in class VII of SMP Negeri 3 Sungguminasa Kab. Gowa.